Moderate physical activity improves inflammatory markers (IL-6 and TNF Alpha) and diabetic profile in prediabetic population - Zubia Shah; Abdul Waheed Mughal; Sherbaz Khan; Saman Tauqir; Inayat Shah (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2021)
Purpose: Prediabetes is a health condition that precedes type 2 diabetes. Globally prevalence of prediabetes is on the rise and approximately 37% of local population are suffering from it. Apart from many other factors, inflammatory markers especially IL-6 and TNF-α play a significant part in development of prediabetes to diabetes. How exercise affects the inflammatory cytokines is elucidated and not completely understood. Methods: A non commercial experimental trail including a total of 48 participants, (36 males and 12 females) with mean age 30.7 ± 7.80 years was carried out after ethical approval and written informed consent. Demographic data, Body plethysmography, exercise parameters, diabetic and inflammatory markers were determined at pre- and post-interventional stage. The exact intensity of exercise capable of eliciting the required heart rate was determined and each participant was asked to perform moderate intensity exercise (45 minutes including warm up and cool down) for 5 days a week for 12 weeks. Results: Twelve weeks of moderate intensity aerobic exercise at (55% to 65% of PMHR) had significant positive effects on body composition including BMI (<0.001), weight (<0.001), diabetic parameters (FBS (0.02), HbA1c (0.001)) and inflammatory parameters (IL-6 (0.018), and TNF-α (0.02)). The effects were identical for males and females with mild differences. Conclusion:Moderate intensity exercise significantly decreases the levels of circulating inflammatory cytokines. Moderate intensity aerobic exercise is easy to incorporate in lifestyle of prediabetic population and can be used as one of the effective strategies for prevention of development of diabetes.